Placement of a Peripherally Inserted Central Catheter in a Prone Patient With COVID-19: Feasibility and Case Report. Issue 4 (July 2021) - Kelly, Linda; Dreher, Denise; Kim, Georgia; Hughes, Timothy; Sabouri, A. Sassan
Abstract : The emergence of the coronavirus disease 2019 (COVID-19) virus has increased in patients with acute respiratory distress syndrome (ARDS). The use of prone positioning during COVID-19–associated ARDS has led to improved oxygenation and decreased mortality. Extended hours of proning may delay or prevent traditional approaches to central vascular access, such as jugular, subclavian, or femoral cannulation. A peripherally inserted central catheter (PICC) is a viable option for prone patients. This article presents a PICC placement in a 56-year-old man with COVID-19 ARDS who required 20- to 24-hour prone positioning during his care in the intensive care unit. Insertion of a PICC while the patient is prone expedites lifesaving medications and infusions without waiting for the patient to be stable enough to be turned to the supine position.